Circulating Ki67 positive lymphocytes in multiple myeloma and benign monoclonal gammopathy. Issue 9 (September 1995) - Miguel-Garcia, A; Matutes, E; Tarin, F; Garcia-Talavera, J; Miguel-Sosa, A; Carbonell, F; Catovsky, D
Abstract : AIMS–To estimate the proportion and nature of the proliferating (Ki67+) circulating lymphocytes in a series of patients with multiple myeloma and monoclonal gammopathy of unknown significance (MGUS) and to correlate this with other clinical and laboratory parameters, using blood from healthy adults as a control. To investigate the extent to which the B and T lymphoid components are involved in progression and/or control of disease. METHODS–Blood lymphocytes from 15 patients with multiple myeloma, 10 patients with MGUS and 10 healthy adults were analysed using a sequential double immunoenzymatic staining technique. Antibodies directed against Ki67 were used to detect cells in cycle, CD3, CD4, and CD8 to identify T cells, HLA-Dr as a marker for B cells and activated T cells, and CD11b as a marker for natural killer cells. Polyclonal antibodies directed against the kappa and lambda immunoglobulin light chains were also used to detect B cells. RESULTS–The proportion of proliferating (Ki67+) lymphocytes was significantly higher in patients with multiple myeloma (6.8 +/- 2.6) and MGUS (3.5 +/- 1.1) compared with the normal controls (1.69 +/- 0.3); this was also true when multiple myeloma and MGUS cases were compared. In multiple myeloma and MGUS over 50% of the Ki67+ cells were activated T lymphocytes (CD3+/HLA-Dr+); a minority (11%) were non-clonal B lymphocytes. In contrast to controls (6.7 +/- 1.9), in patients with multiple myeloma and MGUS the proportion of proliferating T cells expressing CD8 (23.6 +/- 12.5 and 15.3 +/- 7.7, respectively) and CD11b (13 +/- 8.7 and 11.6 +/- 3.9, respectively) was higher. In multiple myeloma there was a positive correlation between the proportion of Ki67+ lymphocytes, beta-2-microglobulin concentrations and disease stage. CONCLUSIONS–Although the number of patients investigated is small, this study suggests that Ki67 expression in blood lymphocytes from patients with multiple myeloma may be a good prognostic indicator for aggressive disease and may help to distinguish multiple myeloma from MGUS. The activated proliferating T cells in these diseases may represent an immunological reaction against the tumour.